2019
DOI: 10.1016/j.actaastro.2018.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of radiation in high altitude solid propellant rocket plumes

Abstract: Models and computational schemes are presented to simulate the flow field and radiation in solid propellant rocket plumes at high altitude. Different models are developed to calculate plume radiation induced by both the gas and the dispersed phase of alumina particles. Simulations were made to reproduce a 110 km altitude rocket plume and comparisons with experimental data on the plume radiance are presented. Influence of different physical processes on the simulation of the plume flow field and radiation is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Information on this topic can be found in monographs (Dombrovsky 1996; as well as in (Duval et al, 2004;Ponti et al, 2021;Hao et al, 2022). The effect of micron-sized alumina particles in combustion products of solid propellants on radiation of rocket plumes was studied in (Surzhikov 2004;Shuai et al, 2005;Binauld et al, 2019).…”
Section: Thermal Radiation In Combustion Systems and Fire Safetymentioning
confidence: 99%
“…Information on this topic can be found in monographs (Dombrovsky 1996; as well as in (Duval et al, 2004;Ponti et al, 2021;Hao et al, 2022). The effect of micron-sized alumina particles in combustion products of solid propellants on radiation of rocket plumes was studied in (Surzhikov 2004;Shuai et al, 2005;Binauld et al, 2019).…”
Section: Thermal Radiation In Combustion Systems and Fire Safetymentioning
confidence: 99%
“…It should be recalled that monodisperse approximation is inapplicable for thermal radiation calculations in the case of a strong difference in behaviour of particles of different size. The known examples are: the thermal radiation of particles in plasma spraying [33][34][35][36], the radiation from two-phase combustion products in exhaust plumes of aluminized-propellant rocket engines [37,38], and the radiative cooling of core melt droplets in nuclear fuel-coolant interaction [39,40]. Fortunately, the subsequent calculations showed that it is not the case for the problem under consideration and the monodisperse approximation is really applicable.…”
Section: Infrared Properties Of Water Dropletsmentioning
confidence: 99%
“…Plastinin [5] discussed a newly proposed simulation method for the radiation of solid and liquid propellant engine plumes, and the simulation results of plume radiation based on this model matched well with existing experimental data. Binauld [6] studied the radiation transfer problem in the plumes of high-altitude solid propellant rockets, simulating the plume radiation caused by gas and alumina particles using the proposed computational model. In summary, the simulation calculation methods for polarized radiation transmission and the study of the radiation characteristics of vehicle plumes are relatively mature.…”
Section: Introductionmentioning
confidence: 99%